Glomalin contribution to soil organic carbon under different pasture managements in a saline soil environment - Banegas, Natalia; Dos Santos, Daniel Andrés; Guerrero Molina, Fernanda; Albanesi, Ada; Pedraza, Raúl (Archiv für Acker- und Pflanzenbau und Bodenkunde, 2022)
The glomalin produced by arbuscular mycorrhizal fungi has beneficial effects on soils. We studied the vertical profile of glomalin-related soil protein (GRSP) in pasturelands grown under saline soils and exposed to different management practices. Treatments included haying and grazing of Chloris gayana subject to either N-fertilization or not. We measured mycorrhizal colonization, spores, root biomass, total GRSP, GRSP-carbon (GRSP-C), organic carbon (OC) and total nitrogen (TN). In the meanwhile, we also developed a mathematical procedure to fit continuous power functions to binned soil data. Power decay functions adjusted excellently well the measured data across the 1-meter soil profile. Meaningful increases of root biomass, OC, TN, GRSP and GRSP-C values were associated with grazing and fertilization. Particularly, GRSP-C averaged 1,134 kg C ha −1 at the beginning experiments and increased significantly up to 1,261 kg C ha −1 in grazed and fertilized pastures at the end of the study period. Carbon accounted for between 17% and 50% of GRSP, representing in turn 0.52-1.62% of SOC stock. So, a tropical perennial grass can contribute to the carbon stock in saline soils by promoting production of GRSP. This contribution increases when inputs and cycling of nutrients are enhanced (grazing and N-fertilization).